Tracking sustainability compliance of buildings in rapidly urbanizing Southeastern Nigeria - Chidozie Charles Nnaji; Ini Okonko; Benita Chimzaram Ogbonna (Sustinere: Journal of Environment and Sustainability, 2024)
This study examines sustainability compliance in Southeast Nigeria, a region experiencing rapid economic, social, and environmental changes. The research uses a mixed-methods approach to collect both quantitative and qualitative data from various stakeholders, including enterprises, governments agencies, civil society organizations, and local communities. The findings reveal a complex landscape of sustainability compliance, highlighting gaps and barriers such as inadequate regulatory frameworks, limited resource access, and a lack of awareness and capacity-building initiatives. Additionally, cultural and societal factors significantly influence attitudes and behaviours towards sustainability. The study emphasizes the importance of context-specific approaches to sustainability compliance in a region characterized by unique socio-cultural and economic dynamics. It provides recommendations for policymakers, businesses, and civil society organizations to foster greater sustainability awareness, promote responsible practices, and create an enabling environment for sustainable development. Further research and collaborative efforts are needed to address these challenges and advance sustainability objectives in the Southeast region.